Bacterial Viability of Edwardsiella tarda from Silver Rasbora (Rasbora argyrotaenia) after Infection with Immmersion Methods. Issue 1 (1st July 2022) - Husna, N; Kusdarwati, R; Ulkhaq, M F
Abstract: Silver rasbora (Rasbora argyrotaenia) is a freshwater fishery commodity that has high economic value. However, fulfilling the demand for silver rasbora still relies on catches from nature, so cultivation is needed. The problem that occurs in the cultivation process is the Edwardsiella tarda infection which causes Edwardsiellosis disease. The purpose of this study was to determine the bacterial viability of E. tarda from silver rasbora after infection with immersion methods. The Total Plate Count (TPC) from blood, liver and kidney was taken from infected fish after 14 days immersion with bacterial suspension. The results showed that E. tarda infection had occurred in the blood, liver and kidneys as indicated by an increasing the density of bacteria in each organ along with the increasing of the concentration of infected bacteria. The highest density of E. tarda bacteria infected in silver rasbora was in the blood and the least was in the kidneys.